Teaching high school level perception about the evaluation process in Education Reform - Mena Álvarez, Andrea; Montesinos Salazar, Lisandro (Atenas, 2016)
Herein, the particular consideration of the teachers interviewed in the level of upper secondary education subsystem College of Science and Technology Studies of the State of Chiapas (CECyTECH) addresses. Each question is addressed primarily about the impact assessment by the official institution, achieved in everyday emotional aspects such as: worry, anxiety, threat, fear, disgust, luck, future changes, Integral Reform of Secondary Education Top.